Gifted education current perspectives and issues - Bakken, Jeffrey P.; Obiakor, Festus E.; Rotatori, Anthony F. (Emerald, 2014)
This volume addresses the most current perspectives and issues related to giftedness and is written by leaders in the field. An excellent resource for special educators, administrators, mental health clinicians, school counselors, and psychologists, this volume addresses the different educational issues that impact this population.
Keywords: Education -- Special Education -- Gifted.; Education -- General.; Teaching of gifted students.; Teaching of specific groups & persons with special educational needs.; Education.; Special education.; Gifted children.; elektronické knihy; electronic books